Privatization, Social Impact, and Social Safety Nets - Gupta, Sanjeev; Ma, Henry; Schiller, Christian (Washington, D.C. : International Monetary Fund, 1999)
Privatization promotes economic efficiency and growth, thereby reinforcing macroeconomic adjustment. In the short run, however, it can lead to job losses and wage cuts for workers and higher prices for consumers. This paper discusses these impacts and the fiscal implications of privatization. It then reviews various methods of privatization and finds that public sales and auctions can have more negative effects on workers but maximize the government's revenue gains. Policymakers' options for mitigating the social impact of privatization are surveyed, and experiences under adjustment programs reviewed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet